The Construction of Nationalism in the Novel Student Hidjo and Its Implications for History Learning in Schools - Andi; Ratih Anggie Wardhani (Criksetra: Jurnal Pendidikan Sejarah, 2025)
This study aims to help students understand the values of nationalism in historical novels and increase their literacy interest in history learning. The research employed a qualitative method with a content analysis approach. Data were collected through interviews, questionnaires, document studies, classroom observations, and an analysis of the novel Student Hidjo. The findings reveal that Student Hidjo by Mas Marco Kartodikromo is relevant for use in history learning at high schools, as it contains nationalist values such as love for the homeland, patriotism, the spirit of unity, and the aspiration for independence. Through this novel, students can better comprehend the values of nationalism while fostering their sense of national pride. The study also found that 88% of students preferred learning history through novels rather than textbooks. Moreover, interviews with teachers indicated that this novel successfully enhanced students' reading interest and understanding of history. With its critical narrative on Dutch colonialism and its inspiring themes, this novel is an effective medium for instilling nationalist values and enriching history learning in schools.